The Roles of Transient Receptor Potential Ion Channels in Pathologies of Glaucoma - Ma, Lin; Liu, Xin; Liu, Qing; Jin, Sen; Chang, Heng; Liu, Haixia (Frontiers in Physiology, 2022)
Transient receptor ion potential (TRP) channels are a cluster of non-selective cation channels present on cell membranes. They are important mediators of sensory signals to regulate cellular functions and signaling pathways. Alterations and dysfunction of these channels could disrupt physiological processes, thus leading to a broad array of disorders, such as cardiovascular, renal and nervous system diseases. These effects position them as potential targets for drug design and treatment. Because TRP channels can mediate processes such as mechanical conduction, osmotic pressure, and oxidative stress, they have been studied in the context of glaucoma. Glaucoma is an irreversible blinding eye disease caused by an intermittent or sustained increase in intraocular pressure (IOP), which results in the apoptosis of retinal ganglion cells (RGCs), optic nerve atrophy and eventually visual field defects. An increasing number of studies have documented that various TRP subfamilies are abundantly expressed in ocular structures, including the cornea, lens, ciliary body (CB), trabecular meshwork (TM) and retina. In alignment with these findings, there is also mounting evidence supporting the potential role of the TRP family in glaucoma progression. Therefore, it is of great interest and clinical significance to gain an increased understanding of these channels, which in turn could shed more light on the identification of new therapeutic targets for glaucoma. Moreover, this role is not understood completely to date, and whether the activation of TRP channels contributes to glaucoma, or instead aggravates progression, needs to be explored. In this paper, we aim to provide a comprehensive overview of recent research on TRP channels in glaucoma and to suggest novel targets for future therapeutic interventions in glaucoma.